Study on the evolution of rock damage and blasting characteristics of deep tunnel splitting and drilling with explosives - Shigui FU; Zegong LIU; jinwei QIU; Shuai YANG; Gangjian AN; Guodong QIAO; Xin ZHANG (工程科学学报, 2025)
As mineral resource extraction progresses into deeper regions, the in-situ geological stresses within rock layers increase significantly. Consequently, high geological stress becomes a critical factor to consider during blasting operations in deep rock formations. This paper establishes a theoretical model for cutting seam blasting to explore the mechanism by which it fractures the rock. Through theoretical analysis, it further examines the impact of geological stress on rock fracturing under cutting seam blasting loads. The results show that geological stress reduces the stress intensity factor at the crack tip and requires higher explosive pressure to propagate subsequent cracks. A comparison of existing experimental data with numerical simulation resulted in the development of a constitutive model (RHT model) to simulate the fracture propagation process of rock under cutting seam blasting loads. This model is further refined to create a three-dimensional numerical model for twin-hole cutting seam blasting under varying geological stress conditions. The study examines internal damage and crack evolution in the rock mass during deep tunnel excavation using cutting seam blasting technology influenced by geological stress. The findings are summarized as follows: (1) In the near-blast zone, geological stress causes the ratio of crushed zone diameters along the cutting seam and noncutting seam directions to range between 1.5 and 2.0, which promotes crack propagation along the cutting seam direction while suppressing crack development in the noncutting seam direction. (2) In the far field, geological stress significantly affects the speed and length of crack propagation. When the cutting seam direction is perpendicular to the maximum principal stress direction, geological stress inhibits crack growth along the cutting seam and reduces both propagation speed and final crack length. (3) Geological stress does not alter the pattern of inter-hole stress changes during twin-hole cutting seam blasting, as stress attenuation and superposition zones are consistently observed between the holes. However, it affects the peak stress at various inter-hole points, with higher geological stress resulting in larger peak stresses at these locations. (4) Geological stress also influences the rock damage induced by cutting seam blasting loads, particularly along the direction of the maximum principal stress. The directional effect of blasting is most pronounced when the cutting seam direction aligns with the maximum principal stress direction. Finally, to analyze the damage caused by blasting excavation in deep tunnels under varying geological stress conditions, a three-dimensional numerical model of deep tunnel blasting excavation is developed. The results indicate that geological stress has a significant impact on the blasting excavation process in deep tunnels. The use of cutting seam blasting in peripheral holes, combined with a delayed detonation sequence for smooth blasting, improves the quality of rock precracking and significantly enhances the stability of the surrounding rock mass. The reliability of the numerical simulation results is further validated through a comparison of the excavation outcomes of three blasting methods at the actual project site. These findings offer valuable guidance for deep tunnel blasting excavation and serve as a useful reference for designing blasting schemes.